Automobile dependence: A contributing factor to poorer health among lower-income households. (March 2018) - Rachele, Jerome N.; Sugiyama, Takemi; Turrell, Gavin; Healy, Aislinn M.; Sallis, James F.
Abstract: Lower household income is one of the strongest predictors of poor health. In this viewpoint, we explore an understudied pathway between household income and health: automobile dependence. We argue that the provision of policies that reduce automobile dependence, and facilitate active and affordable modes of travel (i.e. walking, cycling and public transport), may mitigate poorer health among individuals from lower-income households. Policies and environments that support active travel are likely to have particularly strong health and economic benefits for lower-income residents.